The e-Learning Method for Teaching Mathematical Content in the COVID-19 Era - et al., Yersi Luis Huamán-Romaní (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The technological progress in the social field in a sudden way, specifically in the pedagogical field due to the spread of COVID-19, has had to force and use new teaching and learning strategies. As one of these many teaching processes is the method known as e-learning, which has become more valuable and very important in these times due to the rapid spread of the COVID-19 pandemic. The research method applied is descriptive, correlational, cross-sectional and predictive. The sample applied in this research is 608 students of the 5th grade of secondary education in the province of Sullana, Piura region of Peru. The results reveal the existence of a very significant influence in almost all the dimensions of the study. The dimensions with the highest association values are participation-autonomy, outcome resolution, decision concepts and decision outcomes. The dimensions with the lowest strength of association are undoubtedly the motivation rating, which can be interpreted as meaning that motivation does not have a strong influence on the results. It can be concluded that the application of the e-learning method in the teaching of 5th grade high school students in the area of mathematics is positively valued, although a strong incidence of the method on the grades is not observed, due to the fact that a lower percentage of students were unaware of the application of information and communication technologies for online learning. In addition, women tend to rate autonomy and participation more positively than men when the aforementioned teaching method is applied.